Role of microbiological investigations in the management of non-perineal cutaneous abscesses. Issue 935 (17th September 2003) - Garcea, G; Lloyd, T; Jacobs, M; Cope, A; Swann, A; Berry, D
Abstract : Background: Pus samples for microbiological examination are routinely sent after incision and drainage of abscesses. There is no evidence that microbiology reports influence treatment for non-perineal cutaneous abscesses. Aims: This study assessed (1) how often the microbiology report is used to manage patients' treatment after incision and drainage of an abscess and (2) junior surgical trainees' opinions on sending pus for microbiological examination. Method: A retrospective analysis of the notes of all patients undergoing incision and drainage of abscesses from January 2001 to January 2002 was made. A telephone poll of junior surgical trainees was also undertaken. Results: Most patients, 91%, had specimens referred for microbiology. Of these 43% yielded no growth. Staphylococcus aureus was the most common organism (55.9% of all positive cultures). Anaerobes were a frequent finding from axilla and groin abscesses. Mycobacterium tuberculosis was grown in two patients. Other less common organisms cultured were methicillin resistant S aureus (n=1) and Proteus sp (n=1). Follow up of microbiology reports was found to be inadequate. Conclusion: The bacteria present in non-perineal cutaneous abscesses are, for the most part, predictable. However, a significant number grow less common organisms. It is concluded that pus specimens should be sent routinely for culture and sensitivity and there should be further emphasis on following up microbiology reports by junior medical staff.